Kepemimpinan Perempuan dalam Konstruksi Berpikir Presiden Tiga Negara - Syaiful Amin; Ganda Febri Kurniawan; Andy Suryadi (Universitas Sebelas Maret, 2022)
This study aims to investigate the thought construction of the leaders of three countries, namely Indonesia, the United States and Russia about women's leadership. This research was done by descriptive method. The data for this study was obtained from the official tweets of the presidents of three countries on Twitter. The keywords in the data search were: leadership, women, politics, human rights, and justice. Data analysis was carried out with the Nvivo 12 Pro. The results show that Joe Biden has a stronger thinking construct about women's state leadership with as many as 51, discussed by Joko Widodo in the second position with as many as 49 and Vladimir Putin in the last position with as many as 25. This also answers the thesis that with a liberal democratic system more open to women's leadership compared to the Pancasila democratic system and socialist democracy.